Clinico-Radiological Profile of Neurocysticercosis in Children - Prasad, Prem Lochan; Dawra, Reetika; Chandra, Surabhi (Journal of Nepal Paediatric Society, 2019)
Introduction: Neurocysticercosis (NCC) is the most common parasitic disease of the nervous system caused by the larval stage of Taenia solium (also known as pork tapeworm). Clinical manifestations are pleomorphic and determined mainly by the location, number and viability of cysts as well as by the host response. Neuroimaging is the most useful diagnostic study for parenchymal disease. Methods: The study was conducted in the Paediatric Ward of a tertiary care teaching institute, Bareilly, India. The study was conducted on 50 subjects. The study was a hospital based, prospective, observational study. All admitted children between one year to 18 years and diagnosed to have neurocysticercosis were included the study. Statistical analysis was done by single and double sample proportion test. P value of less than 0.05 was considered significant. Results: Maximum numbers of patients were in age group of five-14 years. Males (62%) were more commonly affected than females. Seizure was found to be the commonest presentation of NCC. In our study majority of cases were diagnosed by CT scan. 70% of the patients enrolled in this study demonstrated ring enhancing lesions on neuroimaging. Maximum number of patients had lesions in the parietal lobe followed by frontal lobe. Conclusions: NCC is common in the age group of five to 14 years. Focal seizures were the most common presentation. Other symptoms were headache and vomiting. Vegetarians were more commonly affected than non vegetarians. Single ring enhancing lesion in parietal area was the commonest neuroimaging findings.